A Critical Analysis of the Explicit and Implicit Treatment of Human Rights Education in Early Childhood Education Textbooks - Martínez-Bello, Vladimir; Martínez-Rojas, Ángela; Lahuerta-Contell, Sara (Frontiers in Education, 2020)
The United Nations Convention on the Rights of the Child explicitly recognizes that children are entitled to the full range of civil, cultural, economic, political and social rights. Despite the powerful social function of early years textbooks in legitimizing cultural norms in primary and secondary education, there has been little attention on human rights issues in early childhood education (ECE) curricular materials. Therefore, this study aims to analyze the explicit and implicit representation of human rights education (HRE) in Spanish ECE textbooks. Our quantitative and qualitative result show that ECE textbooks failed to find any explicit mention of children’s rights; an excessive attention focused on the teaching of responsibilities; a distorted representation of childhood; a lack of representation of those responsible for children's rights; a justification to avoid the adults’ loss of power; and the idea that teaching children as a citizens with rights constitutes inappropriate politicization of the school.